(untitled) (Movimenta (ISSN 1984-4298), 2021)
Aim: The aim of study was verify if respiratory training program the influenced of nitrite/ nitrate (NO-2/NO-3 ) levels in Exhaled Breath Condensate (EBC) in candidate of cardiac surgery. Methods: 21 patients volunteers of both sexes, older, with weakness of inspiratory muscles and candidate operation of coronary artery bypass and/or heart valve surgery admitted in the Clinical Hospital of the Medical School of Ribeirão Preto of São Paulo University (FMRP/USP) were randomized group control (CG=10) patients underwent a minimum of 9 days of inspiratory muscle training using an incentive spirometry "Threshold IMT" with progressive daily increase of load according to patient tolerance and training group (TG=11) patients received only conventional physiotherapay without respiratory muscle training goal. We compared spirometric values, maximal inspiratory pressure, maximal expiratory pressure as well as the values of NO-2/NO-3 in EBC before and after training in each group. Results: It was observed that after spirometry, only peak expiratory flow was very important (p <0.02), increased muscle strength in inspiratory breath in the control group (p <0.03) and group trained (p <0.004). Increase NO-2/NO-3 levels in CEP was significant (p <0.05) only the trained group. Conclusion: The respiratory training protocol, even in the very short term, promoted an improvement in respiratory muscle strength and influenced the concentration of NO-2/NO-3 mediators in CEP, which may suggest that the training may exert some influence on airway inflammation. Further studies with larger samples are needed to determine the benefit of mediator reduction with respiratory muscle strength training.